Perbandingan Sistem Hukum Antara Indonesia dan Malaysia Terkait Peninjauan Kembali - Imam Basuki Rahmanto; Rosdiana Saleh (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Judicial review serves as one of the major backbones of the judicial system in any democratic polity. It ensures the consolidation of democracy because it serves as the principal mechanism of check-and-balance among the three tiers of government in any democratic setting and protects the rights of any aggrieved citizen who is presumed to have been unjustly prosecuted or governed. Given this, the present research focuses on investigating the core ideas of judicial review and its procedures in Indonesia and compares them to Malaysia’s judicial review model and procedures. Ultimately, the present study comes up with a judicial review practice model from the comparative analysis of the judicial review practices of Indonesia and Malaysia. A qualitative research methodology was adopted, and comparative analysis using desktop research design was conducted. It is found from the research that the dualistic judicial review model is quite problematic in terms of application in the Indonesian context, and the institution of the Judicial Ethics Commission (JEC) in Malaysia is likely to be effective for judicial review execution. From the findings, the study suggests a review of the current dualistic judicial review model adopted in Indonesia due to several flaws. The study comes up with an integrated judicial review model based on the comparative analysis of judicial review practices of both Indonesia and Malaysia. This research contributes to the field of legal studies through the four mechanisms of judicial review practice, i.e., judicial independence, easy access to justice, procedural fairness and judicial transparency. It is believed that the integrated model of judicial review and the four mechanisms for judicial review could serve as practical tools for enhanced judicial review practices in Malaysia and Indonesia as well as other countries across the world.